Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 1; b = 2√2; c = -6


= 1. - 6 = - 6


And either of their sum or difference = b


= 2√2


Thus the two terms are 3√2 and -√2


Difference = 3√2-√2 = 2√2


Product = 3√2.-√2 = 3.-2 = -6



using


x(x + 3√2)-√2(x + 3√2) = 0


(x-√2)(x + 3√2) = 0


(x-√2) = 0 or (x + 3√2) = 0


x = √2 or x = -3√2


Roots of equation are √2 or -3√2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics